2019
DOI: 10.1088/1361-6463/ab5311
|View full text |Cite
|
Sign up to set email alerts
|

Mode resolved heating dynamics in pulsed microwave CO2 plasma from laser Raman scattering

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 26 publications
0
48
0
Order By: Relevance
“…It was indeed demonstrated, both experimentally (e.g., van Rooij et al, 2015;Bongers et al, 2017;den Harder et al, 2017;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020 and computationally (e.g., Berthelot and Bogaerts, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019), that in practice, the vibrational non-equilibrium is not the leading mechanism in (sub)atmospheric MW or GA CO 2 plasmas, and that the CO 2 conversion is thermal, although Pietanza et al (2020) suggested to act with caution on this assumption, as their model still showed clear deviations from equilibrium, even at temperatures of 3,500-5,500 K.…”
Section: Improving the Energy Efficiencymentioning
confidence: 72%
See 4 more Smart Citations
“…It was indeed demonstrated, both experimentally (e.g., van Rooij et al, 2015;Bongers et al, 2017;den Harder et al, 2017;van den Bekerom et al, 2019;Wolf et al, 2019Wolf et al, , 2020 and computationally (e.g., Berthelot and Bogaerts, 2017;Heijkers and Bogaerts, 2017;Kotov and Koelman, 2019), that in practice, the vibrational non-equilibrium is not the leading mechanism in (sub)atmospheric MW or GA CO 2 plasmas, and that the CO 2 conversion is thermal, although Pietanza et al (2020) suggested to act with caution on this assumption, as their model still showed clear deviations from equilibrium, even at temperatures of 3,500-5,500 K.…”
Section: Improving the Energy Efficiencymentioning
confidence: 72%
“…In the past decade, many papers, both experimental (e.g., Silva et al, 2014Silva et al, , 2017Klarenaar et al, 2017Klarenaar et al, , 2018Klarenaar et al, , 2019Stewig et al, 2020;Terraz et al, 2020;van den Bekerom et al, 2020) and computational (e.g., Bogaerts, 2014, 2015;Pietanza et al, 2015Pietanza et al, , 2017aPietanza et al, ,b, 2018aPietanza et al, ,b, 2020Bogaerts, 2016, 2018;Capitelli et al, 2017, Heijkers andGrofulović et al, 2018;Silva et al, 2018;Bogaerts, 2018, 2019;Kotov and Koelman, 2019;Terraz et al, 2020), focused on the role of the vibrational kinetics in plasmas, but mainly at low pressure conditions (few mbar up to a few hundred mbar). Most of these studies revealed the importance of the vibrational kinetics at specific conditions (low gas temperature, low pressure) and their contribution to a high energy efficiency.…”
Section: Different Dissociation Mechanisms In Different Plasma Typesmentioning
confidence: 99%
See 3 more Smart Citations